Iron-doped molybdenum oxide synergistically enhanced polycaprolactone breast patch and preparation method thereof
By doping iron into molybdenum oxide nanozyme and introducing it into polycaprolactone, iron-doped molybdenum oxide synergistically enhanced breast patches were prepared, which solved the problem of the lack of anti-tumor function of existing breast patches, and achieved Effective tumor cell killing and mental health improvement.
Patent Information
- Application Number
- CN202411476016.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-03
AI Technical Summary
The existing breast patch lacks anti-tumor function and cannot effectively inhibit tumor recurrence. The defect in breast morphology after surgical resection has a negative impact on the patient's mental health.
Fe-MoOv nanoenzyme is prepared by doping iron in molybdenum oxide nanoenzyme and introduced into polycaprolactone. Hydrothermal reaction and selective laser sintering technology are used to prepare iron-doped molybdenum oxide synergistically enhanced breast supplementation using hydrothermal reaction and selective laser sintering technology. flakes enhance their catalytic activity and photothermal properties.
It improves the anti-tumor performance of breast patches, can accelerate ROS generation under near-infrared light irradiation, achieves the synergistic anti-tumor effect of photothermal/chemodynamic therapy, reduces side effects, and improves tumor cell killing rate.
Smart Images

Figure CN119236164A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of biological scaffold preparation, and in particular to an iron-doped molybdenum oxide synergistically reinforced polycaprolactone breast patch and a preparation method thereof. Background Art
[0002] Breast cancer is one of the most common malignant tumors in women in my country. During the treatment process, mastectomy or total mastectomy is usually required to remove the primary tumor. The defects in breast morphology after resection have a profound impact on the patient's mental health. This morphological change not only affects the patient's appearance, but may also cause problems with self-image and body identity, leading to psychological problems such as anxiety and depression. In recent years, in order to improve the quality of life of postoperative patients, breast reconstruction with breast patch wrapped prosthesis has become an indispensable part of the comprehensive treatment of breast cancer. However, relying solely on surgical resection may not be able to completely eradicate tumor cells, and there is a potential risk of tumor recurrence. Therefore, it is particularly urgent to develop a new breast patch that can provide necessary mechanical support for implanted prostheses and effectively inhibit tumor recurrence.
[0003] Reactive oxygen species (ROS) such as hydroxyl radicals and superoxide anions can cause irreversible oxidative damage to tumor cells by attacking polyunsaturated phospholipid components and destroying DNA structure. Therefore, increasing the level of ROS in the tumor site is an effective strategy to induce tumor cell apoptosis. Nanozymes can specifically produce a variety of ROS due to their responsive characteristics in the tumor microenvironment and their catalytic activity that mimics natural peroxidase or oxidase. They have attracted widespread attention in the field of reactive oxygen-mediated catalytic therapy. Molybdenum-based oxides (MoO x ) is considered to be a nanomaterial with great application potential due to its good biocompatibility, variable valence state of molybdenum ions and biodegradability. 4+ / Mo 5+ / Mo 6+ Redox couple, MoO x MoO exhibits intrinsic oxidoreductase-like properties and can catalyze hydrogen peroxide overexpressed in tumors to generate a large amount of ROS to kill tumor cells. However, the lack of active sites limits the x The catalytic efficiency of β-actin is low, which makes it face great challenges in achieving the ideal anti-tumor effect under dynamic physiological environment.
[0004] By doping elements in MoO x The introduction of oxygen vacancies in nanozymes to increase catalytic active sites is a key factor in regulating the MoO xThe introduction of heteroatoms can disrupt the periodic arrangement of the crystal structure and induce the formation of oxygen vacancies. During the catalytic reaction, oxygen vacancies can provide surface dangling bonds, enhance the adsorption of reaction substrates, and activate the chemical bonds of adsorbed substrates through a large number of local electrons. In addition, abundant oxygen vacancies can enhance the MoO x The localized surface plasmon resonance effect in the near-infrared region gives it excellent photothermal performance and further enhances its catalytic activity, achieving the synergistic anti-tumor effect of photothermal and chemodynamic therapy. x The introduction of nanozymes into polycaprolactone (PCL) breast patches is expected to endow them with excellent anti-tumor functions. Summary of the invention
[0005] In order to solve the problem that conventional breast patches lack anti-tumor function, the present invention provides an iron-doped molybdenum oxide synergistically enhanced polycaprolactone breast patch and a preparation method thereof.
[0006] To achieve the above object, the present invention provides the following technical solution: an iron-doped molybdenum oxide synergistically enhanced polycaprolactone breast patch and a preparation method thereof, comprising the following steps:
[0007] S1. Using ferric chloride hexahydrate as the iron source and ammonium molybdate tetrahydrate as the molybdenum source, Fe-MoO was prepared by hydrothermal reaction. v Nanozymes;
[0008] S2, PCL powder was dispersed in anhydrous ethanol to obtain PCL suspension, and then Fe-MoO v Nanozymes were dispersed into PCL suspension to obtain PCL / Fe-MoO v The mixed suspension was subjected to magnetic stirring, centrifugation, drying, grinding and other steps to obtain PCL / Fe-MoO v Composite powder;
[0009] S3. Put PCL / Fe-MoO v Composite powders PCL / Fe-MoO prepared by selective laser sintering v Breast patch.
[0010] Preferably, in step S1, Fe-MoO is prepared by a hydrothermal method. v Nanozyme, the steps are as follows:
[0011] S11, dissolving ammonium molybdate tetrahydrate in deionized water, adding ethylene glycol, and then adding ferric chloride hexahydrate under constant stirring to completely dissolve the ammonium molybdate tetrahydrate;
[0012] S12, adding a dilute hydrochloric acid solution dropwise to the above solution to adjust the pH value of the solution to acidic, and after a period of magnetic stirring, transferring the mixed solution to a high-pressure reactor for hydrothermal reaction;
[0013] S13, the obtained precipitate was washed with deionized water and anhydrous ethanol, vacuum dried and ground to obtain Fe-MoO v Nanozymes.
[0014] Preferably, in step S1, the molar ratio of molybdenum element to iron element is 8:1-4:1.
[0015] Preferably, in step S12, the pH value of the solution is 2-4.
[0016] Preferably, in step S2, the magnetic stirring time is 0.5-1h, the speed is 500-800r / min, and the temperature is 25-35°C; the centrifugation time is 5-15min, and the centrifugation speed is 6000-10000r / min; the temperature of the vacuum drying oven is 60-80°C, the drying time is 12-24h, and the grinding time is 10-20min.
[0017] Preferably, in step S2, the synthesized Fe-MoO v Nanozymes belong to the monoclinic phase and have a particle size of 50-500nm.
[0018] Preferably, in step S2, the particle size of the PCL powder is 50-150 μm, and the purity is greater than 99%.
[0019] Preferably, in step S12, in step S3, PCL / Fe-MoO v Fe-MoO in breast patch v The mass fraction of nanozyme is 2-8wt%, and the mass fraction of PCL is 92-98%.
[0020] Preferably, in step S3, PCL / Fe-MoO v The composite powder is placed in a selective laser sintering system and sintered layer by layer according to the designed three-dimensional model. During the sintering process, the main process parameters are: laser power is 1-3W, scanning spacing is 0.2-0.8mm, scanning speed is 100-300mm / s, and powder thickness is 0.05-0.15mm.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present invention uses defect engineering technology to design and construct enzyme-mimicking active centers to develop efficient redox nanozymes. xIron is doped into the Fe-MoO to replace some molybdenum ions. This process destroys the periodic arrangement of the crystal structure, thereby inducing the formation of oxygen vacancies. These oxygen vacancies can serve as catalytic active sites, thereby effectively improving the Fe-MoO v Catalytic activity of nanozymes.
[0023] The present invention converts Fe-MoO v Nanozymes were introduced into PCL matrix to prepare composite breast patch, using Fe-MoO v Nanozymes endow the patch with excellent anti-tumor properties.
[0024] Compared with the traditional tumor treatment method, the PCL / Fe-MoO v The breast patch converts hydrogen peroxide in the tumor microenvironment into highly toxic ROS to kill tumor cells, so it has the advantages of few side effects and simple operation. In addition, the PCL / Fe-MoO v Breast patch has excellent photothermal properties. Under near-infrared light irradiation, it can not only produce local thermal effect to damage tumor cells but also further accelerate the generation of ROS, thereby achieving the synergistic anti-tumor effect of photothermal / chemodynamic therapy.
[0025] The present invention adopts SLS technology to prepare breast patches, which can realize customized design according to individual differences to meet actual use needs to the greatest extent, and make it have appropriate porosity and pore size, which is beneficial to the degradation of the patch after implantation, cell adhesion and the exchange of nutrients and metabolites. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the overall process of the present invention;
[0027] Figure 2 The Fe-MoO prepared in Example 1 of the present invention v Transmission electron microscopy image of nanozyme;
[0028] Figure 3 PCL / Fe-MoO prepared in Example 1 of the present invention v Patch and PCL prepared in Comparative Example 1, PCL / MoO prepared in Comparative Example 2 x The ROS content in the cells after the patches were co-cultured with human osteosarcoma MG-63 cells for 1 day;
[0029] Figure 4 PCL / Fe-MoO prepared in Example 1 of the present invention v Patch and PCL prepared in Comparative Example 1, PCL / MoO prepared in Comparative Example 2 x Comparison chart of relative tumor killing rate after 3 days of co-culture of patch and MG-63 cells. DETAILED DESCRIPTION
[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] Example 1, please refer to Figure 1-4 The present invention provides a technical solution: an iron-doped molybdenum oxide synergistically enhanced polycaprolactone breast patch and a preparation method thereof, comprising the following steps:
[0032] Synthesis of Fe-MoO v Nanozymes, using ferric chloride hexahydrate as the iron source and ammonium molybdate tetrahydrate as the molybdenum source, were prepared by hydrothermal reaction of Fe-MoO v Nanozyme, firstly, 2.25g of ammonium molybdate tetrahydrate was dissolved in 60mL of deionized water, 3mL of ethylene glycol was added, and 0.9g of ferric chloride hexahydrate was added under constant stirring to completely dissolve it, and a 19% mass fraction of dilute hydrochloric acid solution was added to the above solution, and the pH value of the mixed solution was adjusted to 3, and the solution turned bright yellow. After magnetic stirring for 30 minutes, the mixed solution prepared above was hydrothermally reacted in an autoclave at 190°C for 6 hours, with a stirring speed of 600r / min and a stirring temperature of 30°C. After the reaction was completed, a black precipitate was collected by centrifugation, and the precipitate was washed 3 times with deionized water and anhydrous ethanol respectively to remove impurities, the centrifugation time was 5 minutes, and the centrifugal speed was 8000r / min. Finally, the precipitate was dried in a vacuum oven at 60°C for 24 hours, and then ground for 10 minutes to obtain Fe-MoO v Nanozymes.
[0033] Preparation of PCL / Fe-MoO v Composite powder, first disperse 19g PCL powder in 200mL anhydrous ethanol and stir magnetically for 30 minutes to obtain PCL suspension; then disperse 1g Fe-MoO v The nanozyme was dispersed into the PCL suspension, treated with ultrasound for 30 minutes, and then dispersed with magnetic stirring for 1 hour at a stirring temperature of 25 °C to obtain a uniformly mixed PCL / Fe-MoO v The suspension was mixed; the suspension was centrifuged and then vacuum dried, the centrifugal time was 10 minutes, the centrifugal speed was 8000r / min, the drying time was 36 hours, the drying temperature was 50°C, and finally the dried powder was ground for 10 minutes to obtain PCL / Fe-MoO v Composite powder.
[0034] Preparation of PCL / Fe-MoOv Breast patch, PCL / Fe-MoO v The composite powder was placed in a 3D printing device and PCL / Fe-MoO was obtained by sintering layer by layer according to the designed 3D model. v For breast patch, the main process parameters are: laser power is 2.0W, scanning interval is 0.5mm, scanning speed is 200m / s, and powder thickness is 0.1mm.
[0035] Example 2
[0036] Synthesis of Fe-MoO v Nanozymes, using ferric chloride hexahydrate as the iron source and ammonium molybdate tetrahydrate as the molybdenum source, were prepared by hydrothermal reaction of Fe-MoO v Nanozyme, first weigh 2.25g of ammonium molybdate tetrahydrate and dissolve it in 60mL of deionized water, add 3mL of ethylene glycol, add 0.72g of ferric chloride hexahydrate under constant stirring to completely dissolve it, add 19% of dilute hydrochloric acid solution to the above solution, adjust the pH value of the mixed solution to 2, and the solution turns bright yellow. After magnetic stirring for 45 minutes, the mixed solution prepared above is hydrothermally reacted in an autoclave at 190°C for 6 hours, the stirring speed is 500r / min, and the stirring temperature is 25°C. After the reaction is completed, the black precipitate is collected by centrifugation, and the precipitate is washed 3 times with deionized water and anhydrous ethanol respectively to remove impurities. The centrifugation time is 10 minutes and the centrifugal speed is 6000r / min. Finally, the precipitate is dried in a vacuum oven at 70°C for 16 hours, and then ground for 15 minutes to obtain Fe-MoO v Nanozymes.
[0037] Preparation of PCL / Fe-MoO v Composite powder, first disperse 19.6g PCL powder in 200mL anhydrous ethanol and stir magnetically for 30 minutes to obtain PCL suspension; then disperse 0.4g Fe-MoO v The nanozyme was dispersed into the PCL suspension, treated with ultrasound for 30 minutes, and then dispersed with magnetic stirring for 1 hour at a stirring temperature of 25 °C to obtain a uniformly mixed PCL / Fe-MoO v The suspension was mixed; the suspension was centrifuged and then vacuum dried, the centrifugal time was 10 minutes, the centrifugal speed was 8000r / min, the drying time was 36 hours, the drying temperature was 50°C, and finally the dried powder was ground for 10 minutes to obtain PCL / Fe-MoO v Composite powder.
[0038] Preparation of PCL / Fe-MoO v Breast patch, PCL / Fe-MoO vThe composite powder was placed in a 3D printing device and PCL / Fe-MoO was obtained by sintering layer by layer according to the designed 3D model. v For breast patch, the main process parameters are: laser power is 1.0W, scanning interval is 0.2mm, scanning speed is 100m / s, and powder thickness is 0.05mm.
[0039] Example 3
[0040] Synthesis of Fe-MoO v Nanozymes, using ferric chloride hexahydrate as the iron source and ammonium molybdate tetrahydrate as the molybdenum source, were prepared by hydrothermal reaction of Fe-MoO v Nanozyme, first weigh 2.25g of ammonium molybdate tetrahydrate and dissolve it in 60mL of deionized water, add 3mL of ethylene glycol, add 0.45g of ferric chloride hexahydrate under constant stirring to make it completely dissolved, add 19% of dilute hydrochloric acid solution to the above solution, adjust the pH value of the mixed solution to 4, the solution turns bright yellow, stir magnetically for 1 hour, and hydrothermally react the mixed solution prepared above in an autoclave at 190°C for 6 hours, with a stirring speed of 800r / min and a stirring temperature of 35°C. After the reaction is completed, centrifuge to obtain a black precipitate, and wash the precipitate with deionized water and anhydrous ethanol for 3 times to remove impurities, the centrifugation time is 15 minutes, and the centrifugal speed is 10000r / min. Finally, the precipitate is dried in a vacuum oven at 80°C for 12 hours, and then ground for 20 minutes to obtain Fe-MoO v Nanozymes.
[0041] Preparation of PCL / Fe-MoO v Composite powder, first disperse 18.4g PCL powder in 200mL anhydrous ethanol and stir magnetically for 30 minutes to obtain PCL suspension; then disperse 1.6g Fe-MoO v The nanozyme was dispersed into the PCL suspension, treated with ultrasound for 30 minutes, and then dispersed with magnetic stirring for 1 hour at 25 °C to obtain a uniformly mixed PCL / Fe-MoO v The suspension was mixed; the suspension was centrifuged and then vacuum dried, the centrifugal time was 10 minutes, the centrifugal speed was 8000r / min, the drying time was 36 hours, the drying temperature was 50°C, and finally the dried powder was ground for 10 minutes to obtain PCL / Fe-MoO v Composite powder.
[0042] Preparation of PCL / Fe-MoO v Breast patch, PCL / Fe-MoO v The composite powder was placed in a 3D printing device and PCL / Fe-MoO was obtained by sintering layer by layer according to the designed 3D model. vFor breast patch, the main process parameters are: laser power is 3.0W, scanning interval is 0.8mm, scanning speed is 300m / s, and powder thickness is 0.15mm.
[0043] Comparative Example 1
[0044] 20g PCL powder was placed in a 3D printing device and sintered layer by layer according to the settings of the 3D modeling software to prepare a breast patch. The steps for preparing the breast patch were as follows: preheating the powder to a temperature slightly lower than the melting point; spreading the powder with a powder roller; sintering the powder layer by layer with a laser beam; removing the excess unsintered powder to obtain a PCL breast patch. The main process parameters during the sintering process were: laser power of 2.0W, scanning spacing of 0.5mm, scanning speed of 200m / s, and powder thickness of 0.1mm.
[0045] Comparative Example 2
[0046] Synthetic MoO x Nanozymes were prepared by a simple hydrothermal method using ammonium molybdate tetrahydrate as the molybdenum source. v Nanozyme, weigh 2.25g of ammonium molybdate tetrahydrate and dissolve it in 60mL of deionized water, then add 3mL of ethylene glycol, add 19% of dilute hydrochloric acid solution to the above solution, adjust the pH value of the solution to 3, and after magnetic stirring for 45 minutes, the mixed solution prepared above is hydrothermally reacted in an autoclave at 190°C for 6 hours. After the reaction is completed, the black precipitate is collected by centrifugation, and the precipitate is washed 3 times with deionized water and anhydrous ethanol respectively to remove impurities. The centrifugal time is 10 minutes, and the centrifugal speed is 8000r / min. Finally, the precipitate is dried in a vacuum oven at 60°C for 24 hours, and then ground for 10 minutes to obtain MoO x Nanozymes.
[0047] Preparation of PCL / MoO x Composite powder, first disperse 19g PCL powder in 200mL anhydrous ethanol and stir magnetically for 30 minutes to obtain PCL suspension; then disperse 1g MoO x Nanozymes were dispersed into PCL suspension, treated with ultrasound for 30 min, and then dispersed with magnetic stirring for 1 h at 25 °C to obtain a uniformly mixed PCL / MoO x Mix the suspension; centrifuge the suspension for 10 minutes at a centrifugal speed of 8000 r / min, dry for 36 hours at a drying temperature of 50°C, and finally grind the dried powder for 10 minutes to obtain PCL / MoO x Composite powder.
[0048] Preparation of PCL / MoO x Breast patch, PCL / MoO xThe composite powder is placed in a 3D printing device and sintered layer by layer according to the settings of the 3D modeling software to prepare a breast patch. The steps of preparing the breast patch are as follows: preheating the powder to a temperature slightly below the melting point; spreading the powder with a powder roller; sintering the powder layer by layer with a laser beam; removing the excess unsintered powder to obtain PCL / MoO x For breast patch, the main process parameters during the sintering process are: laser power of 2.0W, scanning spacing of 0.5mm, scanning speed of 200m / s, and powder thickness of 0.1mm.
[0049] The PCL / Fe-MoO prepared in Example 1 was used to v The PCL patch prepared in Comparative Example 1 and the PCL / MoO2 patch prepared in Comparative Example 2 x The patches were subjected to ROS fluorescence staining test. MG-63 cells were seeded in a 48-well plate at a density of 40,000 cells per well. After culturing for 1 day, breast patches were added and co-cultured for another day. PCL / Fe-MoO v +NIR group power is 1W / cm -2 The cells were irradiated with near-infrared laser for 10 min. At the set time, the cells were stained using a staining kit to evaluate the intracellular ROS content.
[0050] The results of ROS fluorescence staining are shown in Figure 3 As shown, it can be seen that PCL / Fe-MoO v The ROS content of tumor cells in the PCL / MoO x This is because the iron doping increases the Fe-MoO v The catalytic activity of nanozymes can catalyze hydrogen peroxide to generate more ROS. In addition, PCL / Fe-MoO v The ROS content of the +NIR group was the highest, indicating that under near-infrared light irradiation, PCL / Fe-MoO v The catalytic activity of oxidative stress is further enhanced, and the generated ROS can cause irreversible oxidative damage to tumor cells.
[0051] MG-63 cells were seeded in a 48-well plate at a density of 10,000 cells per well. After culturing for 1 day, the PCL / Fe-MoO v and PCL, PCL / MoO x The patch was co-cultured with MG-63 cells for 3 days, during which PCL / Fe-MoO v +NIR group used 1W / cm2 of power per day -2 The cells were irradiated with near-infrared laser for 10 minutes, and then a cell counting reagent (CCK-8) was added. The absorbance was measured at 450 nm, and the anti-tumor efficiency of the emulsion was calculated according to the following formula:
[0052] Antitumor efficacy = ((CCK8 PCL组 -CCK8 空白组 )-(CCK8 实验组 -CCK8 空白组 )) / (CCK8 PCL组 -CCK8 空白组 )×100%, among which CCK8 PCL Group, CCK8 空白组 and CCK8 实验组 They correspond to the absorbance of the PCL group patch, complete culture medium, and the experimental group patch co-cultured with MG-63 cells after adding CCK-8 reagent.
[0053] Antitumor efficacy results Figure 4 As shown, it can be seen that PCL / Fe-MoO v The patch showed significant anti-tumor effect compared with PCL / MoO x Patch, PCL / Fe-MoO v The relative tumor killing rate of the patch increased to 64.9%, and further increased to 86.7% under near-infrared irradiation.
[0054] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An iron-doped molybdenum oxide synergistically reinforced polycaprolactone breast patch and a preparation method thereof, characterized in that: The following steps are involved: S1. Using ferric chloride hexahydrate as the iron source and ammonium molybdate tetrahydrate as the molybdenum source, Fe-MoO was prepared by hydrothermal reaction. v Nanozymes; S2, PCL powder was dispersed in anhydrous ethanol to obtain PCL suspension, and then Fe-MoO v Nanozymes were dispersed into PCL suspension to obtain PCL / Fe-MoO v The mixed suspension was subjected to magnetic stirring, centrifugation, drying, grinding and other steps to obtain PCL / Fe-MoO v Composite powder; S3. Put PCL / Fe-MoO v Composite powders PCL / Fe-MoO prepared by selective laser sintering v Breast patch.
2. The iron-doped molybdenum oxide synergistically reinforced polycaprolactone breast patch and preparation method thereof according to claim 1, characterized in that: In step S1, Fe-MoO is prepared by hydrothermal method. v Nanozyme, the steps are as follows: S11, dissolving ammonium molybdate tetrahydrate in deionized water, adding ethylene glycol, and then adding ferric chloride hexahydrate under constant stirring to completely dissolve the ammonium molybdate tetrahydrate; S12, adding a dilute hydrochloric acid solution dropwise to the above solution to adjust the pH value of the solution to acidic, and after a period of magnetic stirring, transferring the mixed solution to a high-pressure reactor for hydrothermal reaction; S13, the obtained precipitate was washed with deionized water and anhydrous ethanol, vacuum dried and ground to obtain Fe-MoO v Nanozymes.
3. The iron-doped molybdenum oxide synergistically reinforced polycaprolactone breast patch and preparation method thereof according to claim 1, characterized in that: In the step S1, the molar ratio of the molybdenum element to the iron element is 8:1-4:
1.
4. The iron-doped molybdenum oxide synergistically reinforced polycaprolactone breast patch and preparation method thereof according to claim 2, characterized in that: In step S12, the pH value of the solution is 2-4.
5. The iron-doped molybdenum oxide synergistically reinforced polycaprolactone breast patch and preparation method thereof according to claim 2, characterized in that: In step S2, the magnetic stirring time is 0.5-1h, the speed is 500-800r / min, and the temperature is 25-35°C; the centrifugal time is 5-15min, and the centrifugal speed is 6000-10000r / min; the temperature of the vacuum drying oven is 60-80°C, the drying time is 12-24h, and the grinding time is 10-20min.
6. The iron-doped molybdenum oxide synergistically reinforced polycaprolactone breast patch and preparation method thereof according to claim 1, characterized in that: In step S2, the synthesized Fe-MoO v Nanozymes belong to the monoclinic phase and have a particle size of 50-500nm.
7. The iron-doped molybdenum oxide synergistically reinforced polycaprolactone breast patch and its preparation method according to claim 2, characterized in that: In the step S2, the particle size of the PCL powder is 50-150 μm, and the purity is greater than 99%.
8. The iron-doped molybdenum oxide synergistically reinforced polycaprolactone breast patch and preparation method thereof according to claim 1, characterized in that: In step S3, PCL / Fe-MoO v Fe-MoO in breast patch v The mass fraction of nanozyme is 2-8wt%, and the mass fraction of PCL is 92-98%.
9. The iron-doped molybdenum oxide synergistically reinforced polycaprolactone breast patch and preparation method thereof according to claim 1, characterized in that: In step S3, PCL / Fe-MoO v The composite powder is placed in a selective laser sintering system and sintered layer by layer according to the designed three-dimensional model. During the sintering process, the main process parameters are: laser power is 1-3W, scanning spacing is 0.2-0.8mm, scanning speed is 100-300mm / s, and powder thickness is 0.05-0.15mm.